(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2009)
The author concentrates on Deuteronomy 22, the Song of Songs and Ephesians 5. At least three perspectives on aspects of marriage are shown: the ideal marriage gives us a clear indication of the relation between Christ and his church; staying together in marriage is not only based on that feeling of love and excitement: it is also based on the promise or the word given by a man and a wife when they marry, and a marriage should also be acknowledged by the community. The latter are guardians if the man or his wife transgresses the principles of marriage. What is also clear from Deuteronomy is that sexual intercourse is limited to marriage only and that there is no room in marriage for a third person.